A review of recent developments in renewable and sustainable energy systems: Key challenges and future perspective. (March 2020) - Moustakas, K.; Loizidou, M.; Rehan, M.; Nizami, A.S.
Abstract: This editorial prepared for Renewable and Sustainable Energy Reviews as a Virtual Special Issue overviews the research work presented at the NAXOS 2018 6th International Conference on Sustainable Solid Waste Management, held from the 13th June to 16th June 2018 in Naxos Island, Greece. The research work published in this Virtual Special Issue is focused not only on the recent advances in the areas of renewable and sustainable energy systems, but also highlights the key issues and challenges faced with potential solutions and way forward. This editorial summarises the review and original research articles from NAXOS 2018, as well as providing a comprehensive overview of the current trends in the field of renewable and sustainable energy systems. The articles published in this Virtual Special Issue cover a wide range of energy-related topics, including biofuels and bioenergy, biorefineries, wind energy, energy sustainability, biomass, waste to energy technologies, life cycle assessment study, energy and materials recovery from waste and integrated waste management techniques. A total of 29 extended manuscripts were invited, 19 of which were accepted for publication in Renewable and Sustainable Energy Reviews after vigorous review process carried out by expert reviewers in the field with the help of guest editors.